Extraction of copper from pregnant leaching solutions of lead dusts by liquid extraction - Altaibayev, B. T.; Khabiyev, A. T.; Baigenzhenov, O. S.; Bulenbayev, M. Zh; Turan, M. D. (Inst Metallurgy & Ore Beneficiation, 2020)
This paper presents the results of studies of intermediate processing for liquid extraction and re-extraction of copper from sulfate solutions obtained during agitation sulfuric acid leaching of lead dusts, which are technogenic wastes of the Zhezkazgan copper smelter and contain valuable components: more than 38 % lead, 2.4 % iron, 3 % zinc, 3.5% copper, 0.7 % arsenic, etc. The utilization of them can provide additional commercial products and improve the ecological environment of the area where they are located. The article also presents the results of the material balance of the processes of liquid extraction and copper re-extraction.
Keywords: metal impurities; extraction; re-extraction; lead dust; Acorga M5640